Immobilization of enzymatic extract in polyester fiber emulsified with polyurethane resin - Puton, Bruna Maria Saorin; Bernardi, Julia Lisboa; Denti, Andressa Franco; Venquiaruto, Luciana Dornelles; Pedott, Victor de Aguiar; Mignoni, Marcelo Luis; Paroul, Natalia; Dallago, Rogério Marcos (Seven Editora, 2023)
The objective of this work was to evaluate the immobilization of lipolytic and pectinolytic enzymatic extracts in a Polyester Fiber Emulsified with Polyurethane Resin (FPERP) support without and with functionalization with glutaraldehyde. In the first method, the support was emulsified with the enzymatic extract and then the shape of the immobilized was determined before the completion of the polymerization, and could be flat, coiled or double-layered. In the second method, the functionalization of PFRP with glutaraldehyde was performed before immobilization. The esterification activity and operational stability of lipolytic and pectinolytic immobilizes were determined by the synthesis of ethyl oleate and hydrolysis of citrus pectin, respectively. The immobilization of the lipolytic extract in support of PFRP functionalized with 50 and 25% glutaraldehyde resulted in immobilized patients with activity of 28.05 and 15.52 U/g, respectively. On the other hand, the immobilized without functionalization presented higher activity in the form of a double layer (132.17 U/g). The immobilization of the pectinolytic extract resulted in immobilizations with exo-polygalacturonase (exo-PG) and pectinmethylesterase (PME) activity of 1.78 and 12.34 U/g, respectively, for the double-layer immobilized. Regarding operational stability, the immobilized did not present satisfactory values, possibly due to the inefficiency of the polyurethane resin as a support for enzymatic immobilization on the fiber. DOI:https://doi.org/10.56238/alookdevelopv1-163